Aging in America: A Parallel between Popular Images of Aging and Public Policy Narratives. Issue 2 (2nd April 2016) - Keyes, Laura; Dicke, Lisa
Abstract : This article uses discourse theory and identifies images of older adults shaping public policy responses. Rhetorical patterns in narratives of aging shape socially constructed perceptions of aging. The article analyzes how peer-reviewed social science journal articles assessed signs, images, and narratives of older adults in popular media outlets in three eras: pre-1900, 1930–1950, and 1990–2010. A 2 by 2 typology is offered to help with the analysis, because it is useful for making connections between narratives and potential public policy outcomes based on the images presented. The findings illustrate a parallel between negative images and dependency policy narratives, and positive images and emerging policies around individual capability. Public policy makers should recognize the impacts and influences that narratives about individuals and groups may have in shaping opinions and subsequent policy responses.